Attentional Control in Young Drivers: Does Training Impact Hazard Anticipation in Dynamic Environments?. (December 2020) - Yahoodik, Sarah; Yamani, Yusuke
The interaction between top-down and bottom-up processing is a way to characterize control of visual attention, but it has not been extensively applied to the driving domain. The Risk Awareness and Perception Training (RAPT) has been effective in improving drivers' latent hazard anticipation, a top-down process. However, it is unclear whether RAPT protects drivers from being distracted by salient items on the roadway, diminishing latent hazard anticipation. The current driving simulator study examines the potential interaction between bottom-up and top-down processes by having RAPT-and Placebo-trained drivers navigate simulated environments with latent hazards and a stationary or dynamically moving pedestrian. While RAPT-trained drivers were better able to anticipate latent hazards than Placebo-trained drivers, presence of salient, bottom-up stimuli did not negatively impact hazard anticipation performance in either group. This implies RAPT-trained drivers were able to successfully divide their attention, anticipating latent hazards even in the presence of dynamic, driving-relevant objects.